Respuesta :
10, 14, 18 ....
notice, we get the next term by simply adding 4 to the current term, thus "4" is the "common difference, and we know that 10 is the first term.
[tex]\bf n^{th}\textit{ term of an arithmetic sequence} \\\\ a_n=a_1+(n-1)d\qquad \begin{cases} n=n^{th}\ term\\ a_1=\textit{first term's value}\\ d=\textit{common difference}\\ ----------\\ a_1=10\\ d=4\\ n=17 \end{cases} \\\\\\ a_{17}=10+(17-1)(4)\implies a_{17}=10+(16)(4) \\\\\\ a_{17}=10+64\implies a_{17}=74\\\\ -------------------------------[/tex]
[tex]\bf \textit{ sum of a finite arithmetic sequence} \\\\ S_n=\cfrac{n(a_1+a_n)}{2}\qquad \begin{cases} n=n^{th}\ term\\ a_1=\textit{first term's value}\\ ----------\\ a_1=10\\ a_{17}=74\\ n=17 \end{cases} \\\\\\ S_{17}=\cfrac{17(10+74)}{2}\implies S_{17}=\cfrac{17(84)}{2}\implies S_{17}=714[/tex]
notice, we get the next term by simply adding 4 to the current term, thus "4" is the "common difference, and we know that 10 is the first term.
[tex]\bf n^{th}\textit{ term of an arithmetic sequence} \\\\ a_n=a_1+(n-1)d\qquad \begin{cases} n=n^{th}\ term\\ a_1=\textit{first term's value}\\ d=\textit{common difference}\\ ----------\\ a_1=10\\ d=4\\ n=17 \end{cases} \\\\\\ a_{17}=10+(17-1)(4)\implies a_{17}=10+(16)(4) \\\\\\ a_{17}=10+64\implies a_{17}=74\\\\ -------------------------------[/tex]
[tex]\bf \textit{ sum of a finite arithmetic sequence} \\\\ S_n=\cfrac{n(a_1+a_n)}{2}\qquad \begin{cases} n=n^{th}\ term\\ a_1=\textit{first term's value}\\ ----------\\ a_1=10\\ a_{17}=74\\ n=17 \end{cases} \\\\\\ S_{17}=\cfrac{17(10+74)}{2}\implies S_{17}=\cfrac{17(84)}{2}\implies S_{17}=714[/tex]
The answer would be 714.
Common difference =4An=A1+(n-1)dA17=10+(17-1)(4)=10+(16)(4)=10+64=74
Sn=n(a1+an)/2S17=17(10+74)/2=714
Common difference =4An=A1+(n-1)dA17=10+(17-1)(4)=10+(16)(4)=10+64=74
Sn=n(a1+an)/2S17=17(10+74)/2=714